Ag Nanoparticles: Experimental Study of Sign Identification of Nonlinear Refractive Index by Moiré Deflectometry and Z-Scan Methods. (21st October 2013) - Granmayeh Rad, Adeleh; Madanipour, Khosro; Koohian, Ata
Abstract : Two different methods are presented for the sign identification of nonlinear refractive index (n 2 ) of Ag colloidal nanoparticles which are based on nonscanning Moiré deflectometry and Z-scan. In the Moiré deflectometry setup, two lasers are used, one is used as pump laser which causes thermal nonlinear effects in the sample, and the second one is used as the probe laser for monitoring these effects by Moiré deflectometry system. By observing the deflected Moiré fringes, we can determine the sign of nonlinear refractive index in real time, and there would be no need for calibration or complicated calculations. The second technique for sign identification is Z-scan. In this technique, a CW 532 nm second harmonic Nd:YAG laser with a beam power of 55 mW is used as the excitation source. Results show that the nonlinear refractive index is negative for Ag nanoparticles in pure water by both methods.